2016
DOI: 10.4103/0970-4388.180438
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of molar incisor hypomineralization in school children aged 8-12 years in Chennai

Abstract: Prevalence of MIH was 9.7% in the child population residing in Chennai. Males and females were equally affected. The rate of occurrence and severity of MIH are more in the right mandibular first molar. The severity of MIH is more in molars compared to incisors (P < 0.001) and is more in government schools compared to private schools (P = 0.002).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 1 publication
4
19
1
4
Order By: Relevance
“…A study suggested an obvious MIH prevalence decline when the children were older than 10 years old. Similarly, this pooled analysis confirmed that children age younger than 10 years old had higher prevalence of MIH than those who are more than 10 years old.…”
Section: Discussionsupporting
confidence: 71%
“…A study suggested an obvious MIH prevalence decline when the children were older than 10 years old. Similarly, this pooled analysis confirmed that children age younger than 10 years old had higher prevalence of MIH than those who are more than 10 years old.…”
Section: Discussionsupporting
confidence: 71%
“…[ 2 6 ] Worldwide prevalence of MIH shows wide variation ranging from 2.4%–40.2%. [ 3 13 14 ] Weerheijm and Mejà re reported a prevalence rate ranging from 3.6% to 25% after carrying out studies in European countries. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Molar incisor hypomineralization (MIH) is the hypomineralization of systemic origin of one to four permanent first molars, frequently associated with affected incisors. [ 1 2 3 ] It is a qualitative defect of the enamel. It is also called as hypomineralized permanent first molars (PFMs), idiopathic enamel hypomineralization, nonfluoride hypomineralization, and dysmineralized PFMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported a frequency of 7.11% in the children of Nagpur, Mittal and Bharat reported a prevalence of 10.48% in school children residing in Ghaziabad, and Anjum and Sudhan reported a prevalence of 14.9% in children from Jammu. [345678] The secretory phase of the ameloblast is most susceptible to the external environmental factors resulting in a variety of defects. Thus, DDE once formed have a limited ability for alteration.…”
Section: Introductionmentioning
confidence: 99%